Effect of downregulated Î²-catenin on cell proliferative activity, the sensitivity to chemotherapy drug and tumorigenicity of ovarian cancer cells - Wang, J.; Zhou, D.; He, X.; Wang, Y.; Hu, W.; Jiang, L.; Dou, J. (Cellular and Molecular Biology, 2011)
The role of Wnt/Î²-catenin signaling pathway in the etiology and/or progression of ovarian cancer has been well documented. It was domenstrated that ovarian cancer constantly exhibit constitutive activation of canonical Wnt signaling, usually as a result of oncogenic mutations that stabilize and dysregulate the Î²-catenin protein. In this study, we transfected an expression vector-based small hairpin RNA (shRNA) targeting to Î²-catenin encoding gene into human A2780 ovarian cancer cells to investigate the effects of Î²-catenin knockdown on biological characteristics of ovarian cancer cells. The results showed that Î²-catenin shRNA expression resulted in decreased Î²-catenin mRNA and protein expression in the transfected A2780 cells, inhibition of cellular proliferation, decreased capability of clonogenicity in the plating and the soft agar, and increased sensitivities to chemotherapy drugs vincristine, paclitaxel and cisplatin compared to untransfected cells. Importantly, we found that shRNA-mediated knockdown of Î²-catenin strongly decreases tumour growth of human A2780 ovarian cancer cells in xenografts. These results demonstrate that Î²-catenin might be an effective therapeutic target for human ovarian cancer treatment.